2018
DOI: 10.1515/astro-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Defunct Satellites in Nearly Polar Orbits: Long-term Evolution of Attitude Motion

Abstract: Low Earth orbits (LEO) are known as a region of high space activity and, consequently, space debris highest density. Launcher upper stages and defunct satellites are the largest space debris objects, whose collisions can result in still greater pollution, rendering further space missions in LEO impossible. Thus, space debris remediation is necessary, and the LEO region is a primary target of active debris removal (ADR) projects. However, ADR planning requires at least an approximate idea of the candidate objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Melnikov and Shevchenko [23] considered the issue of figuring the Lyapunov season of the disorganized movement region for resonances in satellite movement. Pritykin et al [24] discussed the long-term evolution of attitude motion for defunct satellites in nearly polar orbits. Rosengren et al [25] indicated that the sporadic and random characters of the Global Navigation Satellite Systems' circles mirror a comparative inconsistency in the circles of numerous divine bodies in our solar framework.…”
Section: Introductionmentioning
confidence: 99%
“…Melnikov and Shevchenko [23] considered the issue of figuring the Lyapunov season of the disorganized movement region for resonances in satellite movement. Pritykin et al [24] discussed the long-term evolution of attitude motion for defunct satellites in nearly polar orbits. Rosengren et al [25] indicated that the sporadic and random characters of the Global Navigation Satellite Systems' circles mirror a comparative inconsistency in the circles of numerous divine bodies in our solar framework.…”
Section: Introductionmentioning
confidence: 99%